Estimation of Radiological Effects from Consumption of milk from Volcanic areas of Kisoro, South-western Uganda. - Vianney, Habakwiha,; Bosco, Oruru; Winston, Tumps Ireeta (Journal of Radiation and Nuclear Applications An International Journal, 2023)
Abstract: Determination of activity concentrations of Naturally Occurring Radionuclides in foodstuffs and Radiological Effects from consumption such foodstuffs is very important in assessing internal radiation hazards like cancer to population. The concentration of Naturally Occurring Radionuclides depends on geological formations of specific areas. The aim of this study was to estimate the Radiological effects from consumption of milk from volcanic areas of Kisoro, South-western Uganda. The Radiological Effects that were determined in this study were Radium Equivalent, Annual Effective Dose Equivalent, and Excess Lifetime Cancer Risk. Seventy nine (79) samples of milk were collected from cattle farms in seven sub counties where geological formation was volcanic eruption. Radiological Effects due to Naturally Occurring Radionuclides U-238, Th-232, and K-40 in milk samples were determined. The average activity concentrations were determined using NaI(Tl) detector. The activity concentrations were used to determine the Radiological Effects. The average activity concentrations in milk for U-238, Th-232, and K-40 were; 1.058 Bq l-1, 1.369 Bq l-1, and 19.679 Bq l-1 ,respectively. Average Radium Equivalent was 4.531 Bq l-1, the annual Effective Dose Equivalent was 0.014 mSv y-1 and the Excess Lifetime Cancer Risk was 3 0.041 10 . Samples that were collected from cattle farms that were relatively flat and at lower altitudes had relatively higher activity concentrations hence higher Radiological Effects. The Radium Equivalent, annual Effective Dose Equivalent and, ELCR were all lower than the safe value from consumption of milk by 0.099 Bq l-1 , 0.0019 mSv y-1, and 3 0.005 10 , respectively hence from the results, it is concluded that the milk is safe for human consumption. Since the differences from the safe values are very small, the quantity of milk to be consumed was estimated to be 0.105 litres per day (0.74 litres per week) in order to keep the Radiological Effects low.